A robust strategy for the general synthesis of hierarchical carbons constructed by nanosheets and their application in high performance supercapacitor in ionic liquid electrolyte. (January 2019) - Wang, Dewei; Nai, Jiawang; Li, Hua; Xu, Lang; Wang, Yatong
Abstract: Porous nanocarbons are considered to be one of the key materials for electrochemical energy storage and conversion systems. In the present work, a straightforward one-step technique based on versatile magnesiothermic reduction combined with conventional KOH activation has been developed. We found that the magnesium (Mg) fulfilled multiple roles in the whole reaction and indispensable for achieving control over the organization of 2D nanobuilding blocks. Encouragingly, the same procedures can be successfully applied to a variety of carbon-rich chemicals as carbon sources to produce porous nanocarbons constructed by nanosheets. The intriguing structural features hold a great promise for electrochemical energy storage applications. As a typical example, the resultant HPCMC-1(synthesis from carboxymethylcellulose sodium) possesses unique interconnected carbon sheets network structures with a very large specific surface area and optimal bimodal microporous size distributions. The distinct structural features endow HPCMC-1 electrodes with excellent capacitive storage performance in ionic liquid electrolyte, which show large specific capacitance, good rate capability, long cycling performance and excellent synergetic energy-power outputting capabilities. Considering the general synthetic strategy together with the material sustainability, our work may open up another way for design and controllable fabrication nanocarbon architectures for applications in electrochemical energy storage fields with high performance. Graphical abstract: Image 1